Sintesis Karbon Aktif dari Akar dan Rimpang Lidah Mertua (Sansevieria Trifasciata) sebagai Biosorben Merkuri (Hg) pada Limbah Tambang - Qalifa Mashita Baga; Suleman Duengo; Wiwin Rewini Kunusa; Astin Lukum; Akram La Kilo (Journal of Applied Geoscience and Engineering, 2026)
Mercury (Hg) pollution caused by small-scale gold mining activities poses a serious environmental threat due to its toxic nature, tendency to accumulate, and ability to contaminate water and soil. This study aims to analyse the chemical and morphological characteristics of activated carbon derived from the roots and rhizomes of the snake plant (Sansevieria trifasciata) as a biosorbent, to determine its adsorption capacity in reducing mercury levels in gold mine tailings, and to investigate the influence of biosorbent mass and contact time on adsorption capacity. SEM characterisation results showed that activated carbon had more open pores than unactivated carbon. FT-IR analysis identified the presence of active functional groups, namely –OH, C=C, C–H and C–O, which play a role in the adsorption of mercury ions. The moisture content test yielded a result of 9.2639%, which meets the SNI 06-3730-1995 standard, while the ash content was found to be 17.5682%. Analysis using an atomic absorption spectrophotometer (AAS) showed that the initial mercury concentration in the tailing waste was 0.0263 mg/L and could be reduced to 0.0132 mg/L with 1 g of biosorbent, 0.0045 mg/L with 3 g, and 0 mg/L with 5 g of biosorbent after 360 minutes of contact time.